2020
DOI: 10.1038/s41398-020-0719-8
|View full text |Cite
|
Sign up to set email alerts
|

Long-term probiotic intervention mitigates memory dysfunction through a novel H3K27me3-based mechanism in lead-exposed rats

Abstract: Chronic lead exposure is associated with the development of neurodegenerative diseases, characterized by the long-term memory decline. However, whether this pathogenesis could be prevented through adjusting gut microbiota is not yet understood. To address the issue, pregnant rats and their female offspring were treated with lead (125 ppm) or separately the extra probiotics (1010 organisms/rat/day) till adulthood. For results, memory dysfunction was alleviated by the treatment of multispecies probiotics. Meanwh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
41
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(44 citation statements)
references
References 65 publications
(72 reference statements)
1
41
0
Order By: Relevance
“…Pregnant rats and their female offspring exposed to lead resulted in the loss of dendritic spines in both CA1 and dentate gyrus (DG) regions irrespective of the developmental stages (PND 22 or PND 68). Long-term intervention with multispecies probiotic ( Bifidobacterium longum BL986, Lactobacillus acidophilus LA43, Lactobacillus fermentum LF26, Lactobacillus helveticus LH43, Lactobacillus paracasei LPC12, Lactobacillus rhamnosus LRH10, and Streptococcus therophilus ST30) restored the spine densities in both adolescence and adulthood [ 142 ].…”
Section: Non-therapeutic Modulators Of Dendritic Spinesmentioning
confidence: 99%
“…Pregnant rats and their female offspring exposed to lead resulted in the loss of dendritic spines in both CA1 and dentate gyrus (DG) regions irrespective of the developmental stages (PND 22 or PND 68). Long-term intervention with multispecies probiotic ( Bifidobacterium longum BL986, Lactobacillus acidophilus LA43, Lactobacillus fermentum LF26, Lactobacillus helveticus LH43, Lactobacillus paracasei LPC12, Lactobacillus rhamnosus LRH10, and Streptococcus therophilus ST30) restored the spine densities in both adolescence and adulthood [ 142 ].…”
Section: Non-therapeutic Modulators Of Dendritic Spinesmentioning
confidence: 99%
“…Therefore, it is proposed that treatment strategies directed to the neuronal representations may be more effective in alleviating the lead-induced neurological damages [1]. In one of our previous publications [171], probiotic formulation effectively mitigated lead-led memory deficits by remodeling hippocampal histone modifications in SD rats, which demonstrated the feasibility of epigenetic manipulations in treating lead-led neuronal impairment.…”
Section: Therapeutics For Neurological Disorders Based On Targeting Ementioning
confidence: 93%
“…Gut microbiota dysbiosis has been shown to contribute to the development of AD or other cognition-related psychiatric disorders (Dickerson et al 2017;Hsiao et al 2013). In a recent study, manipulating the gut bacteria in animals using probiotics has been shown to restore the decreased H3K27me3 (trimethylation of histone H3 Lys 27) found in the adult hippocampus and partially prevented the memory dysfunction suggesting that the memory dysfunction could be ameliorated via epigenetic modulators or altering gut microbiota (Xiao et al 2020). miRNAs are a class of small, noncoding RNAs that epigenetically modulate gene expression.…”
Section: Gut Metabolites As Epigenetic Regulatorsmentioning
confidence: 99%